Suplementación con aminoácidos de cadena ramificada en la progresión de la hepatitis crónica (2016)
Malnourishment is a common condition of hepatic failure. Our objective was to evaluate the effect of supplementation with branched-chain amino acid (BCAA) in the diet of rats with chronic hepatitis. Liver damage was generated using carbon tetrachloride (CCl4) for ten weeks in all treatments except control. Experimental units were randomly assigned to six treatments: valine, leucine, isoleucine, three BCAA, CCl4and control, five replicates per treatment, and three animals per experimental unit. Serum albumin concentrations were compare. Tissue injury level was histopathologically graded from zero to three looking for disturbances such as cellular infiltration, fibrosis, and vacuolization. Also, weight gain, food intake, and liver damage signs were monitored. Samples were taken at week 6, 8, and 10. When the effect of treatment was significant (p <0.05) in the analysis of variance, multiple comparisons were adjusted with Tukey-Kramer method. The dietary supplement with BCAA does not alter the progression of fibrogenesis. However, rats under valine treatment showed significantly more weight. Animals in leucine and valine treatments exhibited significantly higher food intake. No signs of liver failure were observed in any treatment. As conclusion, valine and leucine supplementation could have a positive effect in the protein imbalance present in the chronic liver disease.